2012
DOI: 10.1002/jor.22159
|View full text |Cite
|
Sign up to set email alerts
|

The effects of local vanadium treatment on angiogenesis and chondrogenesis during fracture healing

Abstract: This study quantified the effects of local intramedullary delivery of an organic vanadium salt, which may act as an insulin-mimetic on fracture healing. Using a BB Wistar rat femoral fracture model, local vanadyl acetylacetonate (VAC) was delivered to the fracture site and histomorphometry, mechanical testing, and immunohistochemistry were performed. Callus percent cartilage was 200% higher at day 7 (p < 0.05) and 88% higher at day 10 (p < 0.05) in the animals treated with 1.5 mg/kg of VAC. Callus percent mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 25 publications
6
56
1
Order By: Relevance
“…The study which relate organic form of vanadium and angiogenesis, declared that local administration of vanadyl acetylacetonate enhanced femur fracture healing in a nondiabetic BB Wistar rat model, suggesting that local administration of vanadyl acetylacetonate is a potential therapeutic strategy for fracture healing [139]. These results revealed that new blood vessels and VEGFc levels were remarkably increased in the fracture callus [139].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study which relate organic form of vanadium and angiogenesis, declared that local administration of vanadyl acetylacetonate enhanced femur fracture healing in a nondiabetic BB Wistar rat model, suggesting that local administration of vanadyl acetylacetonate is a potential therapeutic strategy for fracture healing [139]. These results revealed that new blood vessels and VEGFc levels were remarkably increased in the fracture callus [139].…”
Section: Methodsmentioning
confidence: 99%
“…These results revealed that new blood vessels and VEGFc levels were remarkably increased in the fracture callus [139]. Although it was found that VEGF expression in mouse epidermal cells after exposure to vanadium (IV and V) was significantly increased [140], no other studies have investigated the effects of vanadium on blood vessel formation [139]. …”
Section: Methodsmentioning
confidence: 99%
“…In a very different type of study, Paglia et al investigated the influence of local administration of VO(acac) 2 at the fracture site on bone healing in healthy, diabetic-resistant, male BB Wistar rats [110]. The results are illustrated in Figure 17 contrasting the progression of healing from 10 to 21 days post-fracture for saline-treated and VO(acac) 2 treated rats.…”
Section: Biological Action Of Vo2+-chelatesmentioning
confidence: 99%
“…A biodegradable magnesium alloy has been studied for orthopedic applications [50] and has been shown to facilitate bone healing in clinical trials [51]. Furthermore, local delivery of vanadium and manganese chloride, both are insulin mimetics, has been shown to enhance bone fracture repair [52,53].…”
Section: Figmentioning
confidence: 99%